Critiques Towards Family Law in Egypt Through the Work of Nawal El Saadawi - Permana, Dede; Naffati, Abdel Kader; Jambunanda, Ahmad Jamaludin (Hukum Keluarga Islam IAIN LANGSA, 2024)
The history of family law reform in Islamic World can't be separated from contributions of the thoughts of the Islamic scholars from time to time. One of them is Nawal el Saadawi's contribution through her criticism of family law in Egypt. This article aims to discuss some of Nawal's criticisms based on two questions. First, what is Nawal el Saadawi's criticism of family law in Egypt? Second, what solution does Nawal offer to realize a family law that - she calls - is just? By answering both of the questions, it is hoped that this study will provide inspiration for academics and legal practitioners in their efforts to find a gender-just family law format. The method used in this research is qualitative with library research, namely by examining library sources that are relevant to the research theme. The results of this research are, first, material in Egyptian family law relating to divorce procedures, polygamy, bait at tho'ah, living and hadhanah, which Nawal considers is still discriminatory towards women. This discrimination occurs because the state ignores patriarchal culture in society. Second, in Nawal's view, efforts to realize just family law must be started from strengthening the principle of freedom of thought among Islamic scholars and legal practitioners.